Exploring Pedagogical Practices in Early Childhood Education: Case Study of ECEC Intervention Community School, Nepal - Tamang, Hira Man; Sherpa, Dawa (Nepal Journal of Multidisciplinary Research, 2025)
Background: Early Childhood Education and Development (ECED) is the foundation of human learning and development. ECED is compulsory for all children in Nepal; however, it is less prioritised in terms of physical infrastructure and teacher management. Thus, this study aimed to explore the pedagogical practices of ECED community schools intervened by the ECEC Innovation in Education. Methods: A qualitative case study design was employed for this study. Classroom observations and in-depth interviews were conducted with teachers, headteachers, and education officers. Focus group discussions (FGDs) were conducted with parents and the chairpersons of the school management committees (SMCs). The interviews and FGDs with the participants were recorded, transcribed and translated to create codes and prepare themes for data analysis. Results: The study revealed that the welcoming behaviour of teachers in the classroom and school with children enhanced children's learning. Children enjoyed the school environment, particularly the teachers' activities and the effective use of learning resources. Teachers used locally available learning resources. The intervention schools have been transformed; however, most of the ECED classes in the community school lacked trained teachers, adequate infrastructure, and necessary learning resources. Conclusion: The school fosters a welcoming, loving, caring, respectful, homely environment that enhance positive behaviour among children. The initiatives and collaborative efforts of teachers, school leaders, and teacher educators contribute to transforming the pedagogical practices of ECED of community-based schools in Nepal. Novelty: This study explored teachers’ welcoming behavior, play-based and activity-based learning, small-group teaching, and the use of local materials as chief ECED practices supporting children’s holistic development.